On the influence of pyrochlore phase on ferroelectric and dielectric properties of PZT thin films - Lima, E. C.; Araujo, E. B. [UNESP]; Eiras, J. A. (Taylor & Francis, 2020)
The intrinsic contribution of dielectric permittivity was obtained in thin films of PZT pyrolyzed at different temperatures. Pyrochlore phases were observed in films pyrolyzed at temperatures above 350 °C, while only the perovskite phase grows in films pyrolyzed at temperatures lower than 300 °C. Dielectric and ferroelectric properties were characterized, and their behaviors were related to pyrolysis temperature. The dielectric permittivity dependence on the bias electric field was investigated at room temperature for different PZT thin films, and these curves were used to reconstruct the hysteresis loops. In this work, a model was used to reconstruct the hysteretic behavior of the films. The experimental results are in excellent agreement with the applied model.
Keywords: nonlinear dielectric properties; permittivity; PZT thin films